2020
DOI: 10.5038/2379-9951.5.1.1122
|View full text |Cite
|
Sign up to set email alerts
|

Bad Inquiry: How Accountability, Power, and Deficit Thinking Hinder Pre-Service Practitioner Inquiry

Abstract: This study of 30 pre-service teachers’ practitioner inquiry papers explores potential pitfalls of practicing inquiry with pre-service teachers. Focusing on the types of questions pre-service teachers ask about student learning, the challenges they face when engaging in inquiry, and the weaknesses of their inquiry products, this paper finds that accountability culture in education, pre-service teachers’ lack of power in the classroom, and deficit thinking left unchallenged by instructors led to weak inquiries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This variation can complicate efforts to define practitioner research, especially for novice researchers such as graduate students. However, there is widespread agreement with Cochran-Smith and Lytle's conceptualization of practitioner research as systematic and intentional (Currin, 2019;Dana & Yendol-Hoppey, 2020;Miller & Shinas, 2019;Schaenen et al, 2012;Schroeder, 2020;Stremmel, 2007). Furthermore, empirical practitioner research differs from other types of practitioner research in that it involves the systematic collection and analysis of data (Cochran-Smith & Lytle, 1993) and is intentional and more visible than reflection, a practice teachers engage in every day (Dana & Yendol-Hoppey, 2020).…”
Section: Terminologymentioning
confidence: 95%
“…This variation can complicate efforts to define practitioner research, especially for novice researchers such as graduate students. However, there is widespread agreement with Cochran-Smith and Lytle's conceptualization of practitioner research as systematic and intentional (Currin, 2019;Dana & Yendol-Hoppey, 2020;Miller & Shinas, 2019;Schaenen et al, 2012;Schroeder, 2020;Stremmel, 2007). Furthermore, empirical practitioner research differs from other types of practitioner research in that it involves the systematic collection and analysis of data (Cochran-Smith & Lytle, 1993) and is intentional and more visible than reflection, a practice teachers engage in every day (Dana & Yendol-Hoppey, 2020).…”
Section: Terminologymentioning
confidence: 95%
“…Moreover, cultural stereotypes and deficit thinking might be roadblocks to persuade teachers to re-conceptualize their preconceived notions about children with disabilities, and view children as capable learners who can benefit from the curriculum [32]. Teachers who employ cultural stereotypes and deficit thinking could easily create inaccurate characterizations of academic ability to children [33] based on race, ethnicity, and special learning accommodations [34]. Therefore, it is critical to prepare teachers and administrators to become more deeply involved in multi-fold issues of equity and design an authentic culturally inclusive learning environment [35].…”
Section: Deficit Thinking and Special Teacher Educationmentioning
confidence: 99%
“…The underlying assumptions were that (i) students with disabilities have inherent deficits and limited abilities and (ii) teachers need to help students with disabilities to overcome their deficits in classrooms [25, 68]. For instance, Schroeder [64] suggested that preservice teachers did not have the power to engage students through inquiry because of deficit‐thinking mindsets. Therefore, the common curriculum‐based intervention usually focuses on fixing or changing students' behaviors in specific disciplines to improve students' academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%